2021
DOI: 10.3389/fonc.2021.716830
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects of I-BET151, an Inhibitor of Bromodomain and Extra-Terminal Domain Proteins

Abstract: I-BET151 is an inhibitor of bromodomain and extra-terminal domain (BET) proteins that selectively inhibits BET family members (BRD2, BRD3, BRD4, and BRDT). Over the past ten years, many studies have demonstrated the potential of I-BET151 in cancer treatment. Specifically, I-BET151 causes cell cycle arrest and inhibits tumor cell proliferation in some hematological malignancies and solid tumors, such as breast cancer, glioma, melanoma, neuroblastoma, and ovarian cancer. The anticancer activity of I-BET151 is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 107 publications
(146 reference statements)
0
7
0
Order By: Relevance
“…BETis are being investigated in clinical trials by increasing their stability and bioavailability, as well as by reducing their DLT. I-BET151, a novel dimethylisoxazole BETi, has been shown to induce G1 phase cell-cycle arrest and apoptosis in leukemic cells by downregulating BCL-2 [ 229 ]. I-BET151 is an I-BET762 analog with an increased in vivo half-life [ 219 ].…”
Section: Therapeutic Targeting Of Histone Modificationsmentioning
confidence: 99%
“…BETis are being investigated in clinical trials by increasing their stability and bioavailability, as well as by reducing their DLT. I-BET151, a novel dimethylisoxazole BETi, has been shown to induce G1 phase cell-cycle arrest and apoptosis in leukemic cells by downregulating BCL-2 [ 229 ]. I-BET151 is an I-BET762 analog with an increased in vivo half-life [ 219 ].…”
Section: Therapeutic Targeting Of Histone Modificationsmentioning
confidence: 99%
“…In cancer cells BRD4 bound Jagged-1 and NOTCH1 promoters, increasing the expression of both components and, thus, NOTCH pathway activation, which promotes proliferation and migration in tumors. In addition, I-BET151 impedes BRD4 binding to the NOTCH1 promoter, diminishing the expression of Hes1 and cancer-cell renewal activity [50,51]. Accordingly, we observed that JQ-1 downregulated Hes-1 and Hey-1 expression in NTS mice.…”
Section: Discussionmentioning
confidence: 53%
“…In cancer cells BRD4 bound Jagged-1 and NOTCH1 promoters, increasing the expression of both components and, thus, NOTCH pathway activation, which promotes proliferation and migration in tumors. In addition, I-BET151 impedes BRD4 binding to the NOTCH1 promoter, diminishing the expression of Hes1 and cancer-cell renewal activity [66,67]. Accordingly, we observed that JQ-1 downregulated Hes-1 and Hey-1 expression in NTS mice.…”
Section: Discussionmentioning
confidence: 53%